1981
DOI: 10.1530/acta.0.0960422
|View full text |Cite
|
Sign up to set email alerts
|

Stroma of human benign prostatic hyperplasia: preferential tissue for androgen metabolism and oestrogen binding

Abstract: Abstract. Because of the well known stromal-epithelial interaction of various urogenital organs, it was of interest to compare quantitatively steroid metabolism and binding in epithelium (E) and stroma (S) of the human benign prostatic hyperplasia (BPH). Testosterone 5α-reductase activity was determined by thin-layer chromatography and androgen as well as oestrogen binding sites by a charcoal adsorption technique after a steroid incubation period of 18 h at 0°C, using methyltrienolone (R1881) and oestradiol-17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
3
1

Year Published

1986
1986
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(61 citation statements)
references
References 0 publications
1
56
3
1
Order By: Relevance
“…Since the involvement of estrogen in stromal hypertrophy is well known, it has been used previously for induction of prostatic hyperplasia in dogs [7]. There is evidence from animal as well as human studies suggesting an important role of the stroma and estrogens in the pathogenesis of benign prostatic hyperplasia (BPH) in man [3, 5 , [2,9,11,12,21,271. Our earlier studies have demonstrated a tenfold higher PIP concentration in benign prostatic tissue and urine (unpublished data) levels of this PIP in BPH patients have also been observed.…”
Section: Discussionmentioning
confidence: 99%
“…Since the involvement of estrogen in stromal hypertrophy is well known, it has been used previously for induction of prostatic hyperplasia in dogs [7]. There is evidence from animal as well as human studies suggesting an important role of the stroma and estrogens in the pathogenesis of benign prostatic hyperplasia (BPH) in man [3, 5 , [2,9,11,12,21,271. Our earlier studies have demonstrated a tenfold higher PIP concentration in benign prostatic tissue and urine (unpublished data) levels of this PIP in BPH patients have also been observed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to epithelial effects, estrogens induce a preferential stimulation of prostate stromal cell proliferation, consequently, combined administration of estrogens with androgens has been used to experimentally induce BPH in dogs [26,27]. In humans, the estradiol:DHT ratio increases moderately within normal prostate epithelial and stromal cells upon aging, however, the increased ratio is massive within BPH tissue which directly implicates estradiol in the disease process [28].…”
Section: Estrogens In the Male And Effects On The Prostate Glandmentioning
confidence: 99%
“…The prostatic epithelium and stroma were separated from each other exactly as described earlier [16], The relative purity of the epi thelial and the stromal fraction was more than 80%, estimated by measuring in both tissue fractions acid phosphatase as a marker for epithelial cells and hydroxyproline as a marker for stromal elements [12,16]. For enzyme measurement, aliquots of the frozen homoge nates were pulverized in a porcelain mortar chilled with liquid nitro gen.…”
Section: Tissue Preparationmentioning
confidence: 99%